2018
DOI: 10.1101/404988
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biotransformation of 2,4-dinitrotoluene in a phototrophic co-culture of engineeredSynechococcus elongatusandPseudomonas putida

Abstract: 16In contrast to the current paradigm of using microbial monocultures in most 17 biotechnological applications, increasing efforts are being directed towards engineering 18 mixed-species consortia to perform functions that are difficult to program into individual 19 strains. Additionally, the division of labor between specialist species found in natural 20 consortia can lead to increased catalytic efficiency and stability relative to a monoculture or 21 a community composed of generalists. In this work, we hav… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Similar phenomena were also observed in some other researches. [ 18,29 ] It has been reported that the chromosomally‐located sucrose catabolose ( csc ) regulon of E. coli W required a relatively high concentration of sucrose (>1%) to activate. [ 30–32 ] Therefore, the accumulation of the basal amount of sucrose might be due to the insensitivity of the CscA system to low sucrose concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Similar phenomena were also observed in some other researches. [ 18,29 ] It has been reported that the chromosomally‐located sucrose catabolose ( csc ) regulon of E. coli W required a relatively high concentration of sucrose (>1%) to activate. [ 30–32 ] Therefore, the accumulation of the basal amount of sucrose might be due to the insensitivity of the CscA system to low sucrose concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Strategies involving co‐cultivation of methanotrophic and oxygenic photosynthetic bacteria in biogas have been already explored (Van der Ha et al ., 2012; Hill et al ., 2017). An engineered Synechococcus elongatus able to convert CO 2 into secreted sucrose can be used in co‐culture with other bacteria to generate biotechnological applications (Löwe et al ., 2017; Weiss et al ., 2017; Fedeson et al ., 2020; Zhang et al ., 2020b).…”
Section: Future Prospectsmentioning
confidence: 99%
“…Alginate encapsulation of S. elongatus 7942 was found to enhance its sucrose production and co-culture stability with polyhydroxybutyrate producing Halomona boliviensis over 5 months, and the encapsulated cyanobacteria resisted invasive microbial species during that time 19 . Moreover, the same alginate-encapsulated sucrose-secreting cyanobacteria (within a barium-alginate hydrogel) and Pseudomonas putida formed a co-culture that both enhanced the degradation of an environmental pollutant, 2,4-dinitrotoluene, and synthesized the biopolymer polyhydroxyalkanoate 6 . As this example demonstrates, hydrogel encapsulation connects individual species that possess different metabolic features, and it supports biological functions over long time periods.…”
mentioning
confidence: 99%